Comparative Effects of Umbilical Cord- and Menstrual Blood-Derived MSCs in Repairing Acute Lung Injury. (27th June 2018) - Ren, Haitao; Zhang, Qiang; Wang, Jinfu; Pan, Ruolang
Abstract : Mesenchymal stem cells (MSCs) can effectively relieve acute lung injury (ALI) in several in vivo models. However, the underlying mechanisms and optimal sources of MSCs are unclear. In the present study, we investigated the effects of umbilical cord- (UC-) and menstrual blood- (MB-) derived MSCs on ALI. MSCs were transplanted into a lipopolysaccharide-induced ALI mouse model, and the therapeutic effects were determined by histological, cellular, and biochemical analyses. Our results showed that both UCMSC and MBMSC transplantation inhibited the inflammatory response and promoted lung tissue repair. UCMSC treatment resulted in reduced damage and inflammation in the lung tissue and enhanced protection of lung function. Furthermore, we found that UCMSCs secreted higher levels of anti-inflammatory cytokines (interleukin-10 and keratinocyte growth factor) in ALI-related conditions, which may be due to the greater therapeutic capacity of UCMSCs compared with MBMSCs. These findings suggest that MSCs protected the lipopolysaccharide-induced ALI model by regulating inflammation, most likely via paracrine factors. Moreover, MSCs derived from the UC may be a promising alternative for ALI treatment.